Entre damas anda el juego: las camareras mayores de Palacio en la edad moderna - López-cordón Cortezo, M. Victoria (Cuadernos de Historia Moderna, 2003)
The «camareras mayores» played a major role in Spanish courtesan life. They were at the core of the female personnel at the Royal house. They were privileged witnesses of the Queen’s personal life and zealous of her privacy, acting as filter between her and the outside world. They also instructed the Queen on the traditions of the Spanish monarchy and gave her advice on the different courtesan factions. Their appointment was therefore a political issue and they were normally mature women, most of them widows, chosen among higher nobility. Their biography is especially interesting to know their peculiarities as a group and to understand the complex social environment in which they lived.
Keywords: Reinas; Corte; Camareras mayores; Casa Real; Facciones cortesanas; Biografías